ANALISIS KESALAHAN DAN PERSEPSI SISWA MENYELESAIKAN SOAL MATEMATIKA DALAM UJIAN BERBASIS KOMPUTER - Ahmat Wakit; Erna Zumrotun; Wulan Sutriyani (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2022)
This research is a descriptive qualitative research. The purpose of this study was to determine students' perceptions in carrying out computer-based tests (CBT) and to describe students' mistakes in solving math problems in CBT. Data collection methods used are questionnaires, interviews and documentation. The research subjects were 1 class majoring in religion and 1 class majoring in science. The results of this study indicate that the average score on the computer-based test (CBT) in religion class is 51.16, the score on algebra questions is 56.96, the score on calculus questions is 54.59, the score on geometry and trigonometry questions is 36.61 and the score on statistics questions. and the odds are 42.06. The average score on the computer-based test (CBT) in the Science class is 35.71, the score on algebra questions is 36.97, the score on calculus questions is 25.71, the score on geometry and trigonometry questions is 23.21 and the score on statistics and probability questions is 42.86. Students' perceptions of computer-based exams are classified as very good. The advantage of CBT is that computer-based exams are more effective, there are warnings if there are unanswered questions, for English questions using a headset so that listening questions are clearer and you don't have to worry about the exam paper being damaged. Meanwhile, the weakness of CBT is that it can hurt the eyes because the light from the computer screen is too bright when carrying out a computer-based exam.Penelitian ini merupakan penelitian kualitatif desktiptif. Tujuan penelitian ini adalah untuk mengetahui persepsi siswa dalam melaksanakan ujian berbasis komputer/computer based test (CBT) dan untuk mendeskripsikan kesalahan siswa menyelesaikan soal matematika SMA dalam CBT. Metode pengumpulan data yang digunakan adalah dengan angket, wawancara dan dokumentasi. Subjek penelitian adalah 1 kelas jurusan keagaman dan 1 kelas jurusan IPA. Hasil penelitian ini menunjukkan bahwa nilai rata-rata ujian berbasis komputer kelas jurusan Keagamaan adalah 51.16, nilai pada soal aljabar 56.96, nilai pada soal kalkulus 54.59, nilai pada soal geometri dan trigonometri 36.61 dan nilai pada soal statistika dan peluang adalah 42.06. Nilai rata-rata ujian berbasis komputer di kelas Jurusan IPA adalah 35.71, nilai pada soal aljabar 36.97, nilai pada soal kalkulus 25.71, nilai pada soal geometri dan trigonometri 23.21 dan nilai pada soal statistika dan peluang adalah 42.86. Persepsi siswa terhadap ujian berbasis komputer tergolong sangat baik. Keunggulan CBT adalah pelaksanaan ujian berbasis komputer lebih efektif, ada peringatan jika ada soal yang belum terjawab, untuk soal Bahasa inggris menggunakan headset sehingga soal listening lebih jelas dan tidak khawatir kertas ujian rusak. Sedangkan kelemahan CBT adalah dapat membuat mata pedih karena cahaya dari layar komputer terlalu terang saat melaksanakan ujian berbasis komputer.